Pengelolaan Ekstrakurikuler Berbasis Karakter Dalam Kurikulum 2013 Di SMK Negeri 2 Surakarta - Noer S, Nitha; , Dr. Eko Supriyanto, S.H, M.H; , Dr.Wafrotur Rohmah, M.M (2015)
This research aims to: 1) Describe the steps extracurricular management planning at State Vocational High School 2 of Surakarta, 2) Describing the implementation of extracurricular based on character at State Vocational High School 2 of Surakarta, 3) Knowing the effective implementation of extracurricular at State Vocational High School 2 of Surakarta. This research is qualitative research with case study research design. Data was collected by interview, observation and documentation. Data analysis technique using an interactive model of analysis, whereas the validity of the data examined by source, technique, and time triangulation method. Results of this research concluded that: 1) Planning of scout extracurricular management in the character formation of students contained in scouting material that refers to the curriculum 2013 and SKU guide book. Scout activities held every once in a week. Facilities and infrastructure are provided including sanggars, sticks, tape, rope, and other tools for these activities can run smoothly. Procurement of infrastructure scout activities using funds from the BOS and the school committee. 2) Implementation of extracurricular based on character especially the scouts includes five characters that are spiritual, emotional, social, intellectual, and physical. Penegak Scout consists of two groups, namely Bantara and Laksana that must fulfill the 23 points of Scout Dasa Dharma in which developed the spiritual, emotional, social, intellectual and physical. 3) Management of character based scout extracurricular at State Vocational High School 2 of Surakarta effectively improve student achievement in academic and non-academic, increase motivation, learning and discipline of students, and the support of parents and the government.